2013
DOI: 10.1016/j.intimp.2013.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Redox markers and inflammation are differentially affected by atorvastatin, pravastatin or simvastatin administered before endotoxin-induced acute lung injury

Abstract: Statins are standard therapy for the treatment of lipid disorders, and the field of redox biology accepts that statins have antioxidant properties. Our aim in this report was to consider the pleiotropic effects of atorvastatin, pravastatin and simvastatin administered prior to endotoxin-induced acute lung injury. Male mice were divided into 5 groups and intraperitoneally injected with LPS (10 mg/kg), LPS plus atorvastatin (10 mg/kg/day; A + LPS group), LPS plus pravastatin (5 mg/kg/day; P + LPS group) or LPS p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 57 publications
1
24
0
Order By: Relevance
“…Eicosapentaenoic acid -enriched phospholipids extracted from sea cucumber Cucumaria frondosa, also has an inhibition effect on the reactive oxygenated species [89,[98][99][100][101][102][103][104][105]. Wu et al [89] remarks that this antioxidant compound alters the metabolic way of the mitochondrial apoptosis [89].…”
Section: Therapy With Antioxidantsmentioning
confidence: 99%
“…Eicosapentaenoic acid -enriched phospholipids extracted from sea cucumber Cucumaria frondosa, also has an inhibition effect on the reactive oxygenated species [89,[98][99][100][101][102][103][104][105]. Wu et al [89] remarks that this antioxidant compound alters the metabolic way of the mitochondrial apoptosis [89].…”
Section: Therapy With Antioxidantsmentioning
confidence: 99%
“…Simvastatin is a cholesterol-lowering agent that reduces local and systemic inflammatory responses through unknown mechanisms 6 Previous data has suggested that simvastatin blocks the activities of many important proinflammatory cytokines, 7,8 such as TNF-alpha and NF-κB. These cytokines are found to be actively involved in apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…At low concentrations ROS and RNS work as signaling molecules, while at high concentrations they damage multiple structures, especially mitochondria [2325, 67, 119, 122, 129, 131]. …”
Section: Pathways Affected By Redox Signaling In I/rmentioning
confidence: 99%
“…Oxidation of these residues forms reactive sulfenic acid, which in turn forms disulphide bonds with nearby cysteines, and undergoes further oxidation into sulfinic or sulfonic acid, or sulfenamide when nitrogen is present locally. These redox modifications are reversible through reducing systems such as thioredoxin and peroxiredoxin [2325, 67, 119, 122, 129, 131]. …”
Section: Pathways Affected By Redox Signaling In I/rmentioning
confidence: 99%
See 1 more Smart Citation